Mapping research on disinformation and misinformation across the Nordic countries: An integrative review - Grahn Hilkka; Kalsnes Bente; Isaksson Elsa; Mayerhöffer Eva; Ólafsson Jón Gunnar; Falkheimer Jesper; Henriksen Frederik Møller; Kristensen Jakob Bæk; Saari Dominic (Nordicom Review)
Social media and artificial intelligence have made it easier than ever to create and widely spread manipulated content. Recent geopolitical and digital developments underscore the need for more research on the topic, even in the Nordic countries with their recognised resilience against dis- and misinformation. This integrative review (N = 359) examines how dis- and misinformation have been studied across disciplines in Denmark, Finland, Iceland, Norway, and Sweden between 2014 and 2024. The diversity of terminology and fields in this research highlights its significance and the potential for cross-disciplinary and cross-border collaboration. The article identifies five main topics within the literature: security and Russia’s actions; media and fact-checking; health; media literacy; and social media. While Nordic countries share similarities in dis- and misinformation research, Finland, Norway, and Sweden are more closely aligned with each other than with Denmark or Iceland. This study also identifies research gaps, including the need for more psychological and cognitive science research on dis- and misinformation. Overall, it provides a more comprehensive understanding of dis- and misinformation in the Nordic countries than previously available.